2016
DOI: 10.1371/journal.pbio.1002395
|View full text |Cite
|
Sign up to set email alerts
|

Hemotin, a Regulator of Phagocytosis Encoded by a Small ORF and Conserved across Metazoans

Abstract: Translation of hundreds of small ORFs (smORFs) of less than 100 amino acids has recently been revealed in vertebrates and Drosophila. Some of these peptides have essential and conserved cellular functions. In Drosophila, we have predicted a particular smORF class encoding ~80 aa hydrophobic peptides, which may function in membranes and cell organelles. Here, we characterise hemotin, a gene encoding an 88aa transmembrane smORF peptide localised to early endosomes in Drosophila macrophages. hemotin regulates end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 71 publications
0
64
0
Order By: Relevance
“…Similarly, it has been suggested that smORFs within LncRNAs, or overlapping annotated coding mRNAs, could function mainly as regulators of transcript stability, by engaging the non-sense mediated decay (NMD) pathway [64][65] . Nonetheless, as shown above, several smORF-encoded peptides with important functions have been identified in previously non-coding RNAs proving that these sequences can certainly encode functional peptides [10,48,[50][51][52]54]. There are even examples of canonical non-coding RNAs, such as pri-miRNAs [66] and ribosomal RNAs [67][68][69], encoding biologically active peptides with well characterised functions.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, it has been suggested that smORFs within LncRNAs, or overlapping annotated coding mRNAs, could function mainly as regulators of transcript stability, by engaging the non-sense mediated decay (NMD) pathway [64][65] . Nonetheless, as shown above, several smORF-encoded peptides with important functions have been identified in previously non-coding RNAs proving that these sequences can certainly encode functional peptides [10,48,[50][51][52]54]. There are even examples of canonical non-coding RNAs, such as pri-miRNAs [66] and ribosomal RNAs [67][68][69], encoding biologically active peptides with well characterised functions.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 91%
“…hemo is expressed in hemocytes (Drosophila macrophages) where it regulates endosomal maturation, and phagocytosis, by inhibiting the activity of phosphotidyl-inositol kinases through an interaction with 14-3-3z ( Figure 2B; [54]). Interestingly, this regulatory mechanism also appears to have been conserved across evolution as the vertebrate Stannin (Snn), a factor involved in organometallic cytotoxicity [55], is the functional Hemo homologue in flies and mouse macrophages [54].…”
Section: Computational and Biochemical Strategies Unravel Novel Smorfmentioning
confidence: 99%
“…APELA annotation has now changed from lncRNA (GRCh37) to mRNA (GRCh38), highlighting the dynamic nature of genome annotations . Other biological roles attributed to smORFs include sarcoendoplasmic reticulum calcium transport ATPase (SERCA) machinery regulation, regulation of ribosome-protein complexes, prevention of cell death, and regulation of transcription (Hashimoto et al 2001;Galindo et al 2007;Kondo et al 2007;Hanyu-Nakamura et al 2008;Escobar et al 2010;Magny et al 2013;Anderson et al 2015;Pueyo et al 2016b;D'Lima et al 2017;Matsumoto et al 2017a, b). Moreover, smORFs have been detected within the mitochondrial genome, encoding short circulating peptides acting in a hormone-like manner (Yen et al 2013;Lee et al 2016;Kim et al 2017;Okada et al 2017).…”
Section: Smorfs: Mrna or Lncrna Orfs Smaller Than 100 Codonsmentioning
confidence: 99%
“…More such investigations conducted in the recent past have indicated a diverse range of functions for sORFs. These include muscle regeneration [22,23] , phagocytosis [24] , DNA replication [25] , cancer [26] and metabolism [27,28] . Despite these examples, the vast majority of novel ORF products have not been investigated rigorously and systematically because most of the past studies have focussed on only sORFs, which encode peptides that are smaller than 100 amino acids, that have been dismissed as functionally inconsequential.…”
Section: Discussionmentioning
confidence: 99%